Endovascular Coil Trapping of a Ruptured Dissecting Aneurysm of the Vertebral Artery Using Detachable Coils and Micro-Tornado® Coils - Kim, Myeong-Soo (Korean Society of Cerebrovascular Surgeons; Korean Society of Endovascular Surgery, 2013)
We experienced a patient with a ruptured dissecting aneurysm of the vertebral artery who was treated by trapping of the lesion using Guglielmi detachable coils (GDCs) with micro-tornado® coils (MTCs). An 80-year-old male was transferred with a ruptured left vertebral artery dissecting aneurysm (VADA). The dissected portion of the vertebral artery was effectively trapped using GDCs and MTCs. The MTCs used for neurointervention were comprised of various types of coils and we successfully placed them into the parent artery of the dissected segment. The author suggests that this case demonstrates the usefulness of endovascular coil trapping of VADAs using MTCs in achievement of embolization.